Pengembangan Kawasan Wisata Bukit Kayoe Putih dalam Prespektif Collaborative Governance - Donarinto, Diccio; Widiyarta, Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze collaborative governance in the management of the Kayoe Putih Hill (BKP) tourist area. This study uses a qualitative research method with a descriptive approach. The theory used in this study is Ansell and Gash's theory, which includes starting conditions, institutional design, facilitative leadership, and collaborative processes. Data collection techniques in this study used interviews, observation, and documentation. The results of this study indicate that the collaborative process carried out in the management of the Kayoe Putih Hill (BKP) tourist area is running well. The collaborative process is carried out by dividing tasks and responsibilities between each party through good communication and cooperation, thus having a positive impact on the management of the Kayoe Putih Hill (BKP) tourist area.